Strategy for approving a universal flu vaccine. (April 2017) - Ben-Yedidia, Tamar; Babecoff, Ron Marc; Arnon, Ruth
An urgent need exists for a universal flu vaccine to be more effective than current vaccines, yet there is no such vaccine in the market and no regulatory guideline for its approval. This report proposes a stepwise process for regulatory and marketing approval for such a vaccine. As a first step, the universal vaccine will be tested as a primer to existing HA-based vaccines. Regulatory approval and conditional marketing authorization will be granted based on safety assessments and improved hemagglutination inhibition antibodies (as a marker for efficacy) for the vaccines used in combination. Permanent market authorization will be granted next, based on clinical efficacy data, accumulated during several years, and ultimately the new vaccine will be approved as a standalone vaccine.